Analysis of Character Education: Challenges and Strategies in the Era of Globalization - Lulu Alwiyah; Muhamad Solukhi; Masduki Duryat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Character education in the era of Globalization faces various complex and dynamic challenges. Rapid technological advances make children spend more time in cyberspace such as playing games and playing social media than opening learning sites and studying teaching materials. In this study, the method used is a qualitative descriptive method with Library Research. The results of the study show that there are several challenges to character education in the era of Globalization, including; gaps in access to technology, the influence of social media, and changes in learning patterns, morality, and lack of supervision. In overcoming these challenges, an efficient strategy is needed.